Protective effects of palm vitamin E on glutamate-induced injury of astrocytes. - Musa, Ibrahim (2012)
Glutamate toxicity is a major contributor to neurodegeneration in the nervous system. In the past few years, palm tocotrienol-rich fraction (TRF) has been shown to provide neuroprotection to neurons against glutamate excitotoxicity. Palm TRF is an extract of palm oil and consists of 25% a-tocopherol and 75% tocotrienols. TRF has been shown to possess potent antioxidant, anti-inflammatory, anticancer, neuroprotection and cholesterol-lowering activities. The main objective of the present study is to observe the effects of vitamin E when given to astrocytes before (pre-treatment) and after (post- treatment) glutamate excitotoxicity. A few parameters were selected; cell viability, mRNA expression of neuron specific enolase (NSE), concentration of glutathione (GSH) in the astrocytes and morphology of the cell. Cell viability was measured by using the MTT assay. NSE which is a type of neurobiological marker was observed by using the Reverse Transcription-Polymerase Chain Reaction (RT-PCR). Finally, cell morphology was monitored under fluorescence microscope by using the acridine orange/propidium iodide (AO/PI) assay. The concentration of glutamate (180mM) used throughout this study was only meant to cause injury to the astrocytes. Three types of vitamin E were used for the cell viability assay; tocotrienol rich fraction (TRF), tocotrienol enriched fraction (TEF) and a-tocopherol. Exposure to 180 mM glutamate resulted in 20% of cells death. There was no significant difference between the viability of the cells that were pre- and post-treated with various concentrations of TRF, TEF and a-tocopherol upon glutamate exposure. In contrast, the mRNA expression of NSE was reduced significantly when treated with TRF, but not tocopherol. At 300 ng ofTRF, the NSE expression for both pre- and post-treatment was reduced by 50%. In addition, the concentration of GSH in cells treated with TRF was higher compared to the cells treated with tocopherol. Further results from the histology studies also showed that TRF not only provide a better protection against glutamate, but also able to reduce the number of necrotic and apoptotic cells. When 300 ng of TRF was given to the astrocytes, the percentage of healthy cells increased to 60% for pre-treatment and 30% for post¬treatment which indicated that even at nanogram concentration, TRF protects the astrocytes against glutamate induced oxidative stress. On the other hand, high concentration of a-tocopherol showed the pro-oxidant effects which promoted cells death at 300 ng of a-tocopherol which increased the expression ofNSE. The percentage of apoptotic and necrotic cell remained high upon tocopherol treatment. The results from the present study demonstrate that tocotrienols, but not a-tocopherol, protect astrocytes against glutamate-induced cells death.